Hukum Perkawinan dalam Masyarakat Hukum Adat Indonesia - Hasna Zahra Wahyuni; Rafli Ramdan; Husnaini Amiroh; Humaeroh Humaeroh (Lembaga Pengabdian Masyarakat Universitas Ichsan Gorontalo, 2026)
This article examines marriage law within Indonesian customary law communities and its interaction with national legal regulations. In customary societies, marriage is not merely a personal bond between a man and a woman, but a social institution involving extended families and the wider community. The study aims to describe the various forms of customary marriage, the requirements for its validity, and the procedures for legalization, including the recognition of marriages among adherents of indigenous belief systems. This research employs a normative juridical approach using statutory and conceptual analysis based on relevant legal provisions and customary practices. The findings show that customary marriage systems in Indonesia are strongly influenced by kinship structures such as patrilineal, matrilineal, and parental systems, resulting in diverse forms including bridewealth marriage, semenda marriage, independent marriage, mixed marriage, and elopement. The validity of marriage in customary law is closely connected to religious or belief-based rituals and community acknowledgment. Furthermore, developments in national law, particularly Law Number 1 of 1974 on Marriage and Constitutional Court Decision Number 97/PUU-XIV/2016, have strengthened legal recognition for followers of indigenous beliefs in marriage registration. The study concludes that customary marriage law remains relevant and continues to coexist with national law, reflecting Indonesia’s legal pluralism and cultural diversity.